Islas Flotantes Artificiales con Achira (canna indica) y Pasto Guinea (panicum maximum), como alternativa para la remoción de Nitratos, Fosfatos y Cromo de Agua Procedente del Río Cutuchi - Bravo De la Cruz, Alex Armando (2019)
The Artificial Floating Islands are a system of phytoremediation of polluted waters, similar to natural wetlands. The objective of this investigation was to evaluate the effect of Canna indica and Panicum maximum on the removal of NO3, PO4 and Cr III in waters from Cutuchi River. For this, a floating island of 0.12 m2 was installed in a body of water of 67 liters (Treatment 1), three repetitions and a witness. The evaluations of the parameters removed were every 21 days and every seven days of the development of the plant during four months. The percentages of removal were: Nitrates 71.96%, Phosphates 53.13% and Chromium 87.08%. The system with the Canna indica and Panicum maximum varieties constitutes an alternative to improve water quality.